University Faculty Development Program at Rawalpindi Medical University - ShaguftaSaeedSial, ShaguftaSaeedSial (Journal of Rawalpindi Medical College, 2019)
Faculty development program refers to all activities taken up by the faculty in an institution targeting their development, both personal and professional, and finally implying the growth of the institution.1 The last two decades have witnessed dramatic changes in various fields of life. In the field of medicine, a paradigm shift has been observed from individualized and conventional approach to evidence based strategies. In Pakistan, the mushroom growth of medical colleges has occurred. The standard of education has deteriorated and recently some new universities have appeared on horizon. In order to thrive, they have to meet these challenges amicably. For a university, the continuous endeavour to excel is mandatory in order to accomplish its goals. They are no longer an institution that imparts degrees, rather they have to focus on improving and improvising medical education, conducting purposeful research and imparting best possible services to the patients and the society. In Pakistan, there is not only a shortage of school teachers but the medical teachers also. Doctors, who join the medical university as teachers, may not be well versed in teaching skills, although they may be good clinicians. As the students of today belong to generation Y, the changes they have observed in last two decades are substantially more in absolute quantity and magnitude than their precedents. Consequently, the generation Y (the millennial) have a higher processing capacity, are more complex and more sophistication than the older generation X (born in 1960-1980). The world has become smaller and sharper, with better resolution and better internet speed. Thus, there is a communication gap between the students and the teachers. Therefore, there is a dire need to change teaching strategies. The curriculum needs to be updated and better aligned to today’s needs. The assessment tools must be revised and more technology-oriented delivery needs to be incorporated rather than the conventional lectures strategy. Thus, improvement in teaching strategies will enhance the quality and capability of graduating doctors. The second challenge faced by the professionals is the patient care, which has to be evidence based. This requires solid evidence through research. The university has to provide an environment where research culture prevails. From Pakistan, the number and quality of medical research articles is far behind that of even the neighbouring countries.2 A dedicated department with adequate staff is mandatory to fulfil this gap. A constant support to the researchers at faculty level is required not only to refresh their knowledge but also to familiarize them with statistical and medical writing capabilities. High quality research brings credentials to the university and improves individual’s portfolio apart from delivering best service to patients. Moreover, the role of university also encompasses the grooming of the professional as a mentor, a leader, a supervisor and an administrator. It is a multifaceted prism that needs to be enlightened. The faculty is an asset of the university. Highly professional faculty will self-perpetuate quality research as well as academic excellence. Ultimately, the university ranking improves as the national and international standards are met. High ranking universities act like a magnets and attract highly motivated professionals who enter into a structured system and contribute positively. The universities although are fully aware of the need but often there is a difficulty in implementation. How to start the program and how to devise a curriculum are big challenges for the faculty of a newly formed universities due to lack of faculty development programs. Rawalpindi medical university (RMU), although being only few months old, has devised a fully structured faculty development program (UFDP) with five main domains to be addressed, i.e. medical education, research, administrative skills, supervisory & leadership skills and patient care.3 Both formal and informal methods are being employed. The strategy focuses more on workshops of one to two days, being conducted regularly throughout the year, symposia, guest lectures, seminars and theme based grand rounds. UFDP upholds the motto of the University i.e. “Wisdom, Truth and Service”. Highly trained and professional faculty of the University has not only won credentials at national and international level but also contributes in escalating the ranking of the University globally. Moreover, the first and the foremost aim of a professional doctor is explicitly achieved, as ‘the patient deserves the best’. The learning objectives, need assessment, audit, quality assurance, feedback, tangible scoring, monitoring, supervision and funding of the workshops were finalized under the able advice of Vice Chancellor, RMU.4 The UFDP of RMU is expected to serve as a role model for other universities so that they can move closer to their cherished goals.